P1793MICROBIAL URETERAL STENT COLONIZATION IN KIDNEY TRANSPLANTATION: INCIDENCE AND IMPACT IN URINARY TRACT INFECTION AND RENAL FUNCTION. (6th June 2020) - Rau, Melissa; Carrera Salinas, Anna; Marti, Sara; Fiol, Maria; Etcheverry, Begoña; Riera, Luis; Ardanuy Tisaire, Carmen; Melilli, Edoardo
Abstract: Background and Aims: Ureteral stent insertion is nowadays a common practice in kidney transplantation, leading to a dramatic reduction of surgical issues. On the other hands, urinary tract infections are the most common complication in the first months after transplant. Main scope of our study was to analyze the incidence of stent colonization and its impact on the development of urinary tract infection (UTI) in the first six months after transplantation Method: Prospective observational study including 23 consecutively recruited patients at one single center. Patients with a previous history of surgical intervention on urinary tract before transplant were excluded. Pigtail stents were removed as for local protocol between 3 and 4 weeks after transplantation in aseptic condition and were cut in a half (proximal and distal) and analyzed separately. Stent colonization were detected by sonication method. Urine culture timing are depicted in Figure 1 . In case of clinical symptoms, extra urine cultive were performed as for clinical practice. Patient were followed for 6 months, and results of stent colonization were blinded to clinicians. Results: Table 1 shows main characteristic of our cohort. Conclusion: